Variation of he diameter and percentage of medulation in the fibre of Huacaya alpacas (Vicugna pacos) - Olarte D., Ceferino U. (2023)
To identify variations in fibre diameter in the type of medullation in Huacaya alpacas from the La Raya Experimental Centre, Puno; 6 g of fibre from the left side of the middle ribcage of 190 alpacas were collected, considering the factor sex (males: 89; females: 109) and age group (I: 1-2; II: 3-4; III: 5-6). ; IV: 7-8; V: 9-10 years). The variables considered included non-medullated fibres, with fragmented medulla, continuous medulla, discontinuous medulla and strongly medullated fibres with their respective percentages. The fibres were analysed using FIBER MED equipment and the evaluation of the percentages were subjected to Bliss angular transformation to obtain arcsine values. A 2x5 factorial arrangement was used under a completely randomized design. Also, Spearman correlation was determined. The average fibre diameter (AFD) increased with age (p<0.05). The percentage of total medullated fibres (TPM) increased from 34.79% in the 1-2 years group to 74.72% at 9-10 years (p<0.05) and the percentage of non-medullated fibres (NFM) decreased from 65.69 to 25.60% (p<0.05). The most notable correlations were between TMP and AFD (r=0.883) and between FNM and AFD (r=-0.883). It is concluded that in Huacaya alpacas the diameter of medullated fibres is greater than that of non-medullated fibres, whereas the percentages of medullated fibres are greater than those of non-medullated fibres.